Metformin Suppresses Expression of the Selenoprotein P Gene via an AMP-activated Kinase (AMPK)/FoxO3a Pathway in H4IIEC3 Hepatocytes - Takayama, Hiroaki (American Society for Biochemistry and Molecular Biology, 2014)
Selenoprotein P (SeP; encoded by SEPP1 in humans) is a liver-derived secretory protein that induces insulin resistance in type 2 diabetes. Suppression of SeP might provide a novel therapeutic approach to treating type 2 diabetes, but few drugs that inhibit SEPP1 expression in hepatocytes have been identified to date. The present findings demonstrate that metformin suppresses SEPP1 expression by activating AMP-activated kinase (AMPK) and subsequently inactivating FoxO3a in H4IIEC3 hepatocytes. Treatment with metformin reduced SEPP1 promoter activity in a concentration- and time-dependent manner; this effect was cancelled by co-administration of an AMPK inhibitor. Metformin also suppressed Sepp1 gene expression in the liver of mice. Computational analysis of transcription factor binding sites conserved among the species resulted in identification of the FoxO-binding site in the metformin-response element of the SEPP1 promoter. A luciferase reporter assay showed that metformin suppresses Forkhead-response element activity, and a ChIP assay revealed that metformin decreases binding of FoxO3a, a direct target of AMPK, to the SEPP1 promoter. Transfection with siRNAs for Foxo3a, but not for Foxo1, cancelled metformin-induced luciferase activity suppression of the metformin-response element of the SEPP1 promoter. The overexpression of FoxO3a stimulated SEPP1 promoter activity and rescued the suppressive effect of metformin. Metformin did not affect FoxO3a expression, but it increased its phosphorylation and decreased its nuclear localization. These data provide a novel mechanism of action for metformin involving improvement of systemic insulin sensitivity through the regulation of SeP production and suggest an additional approach to the development of anti-diabetic drugs.